Application and commercial value of traditional Chinese auspicious patterns in modern jewellery design - Hong, Yao; Alli, Hassan; Shaari, Nazlina (Human Resources Management Academic Research Society (HRMARS), 2024)
This study explores the application of traditional Chinese auspicious patterns in modern jewellery design and their commercial value. Through literature review, image analysis and case studies, the study found that these auspicious patterns not only enrich the cultural connotation of modern jewellery design, but also give jewellery works unique value and market appeal. The beautiful meanings and traditional culture carried by auspicious patterns make jewellery works not only ornaments, but also carriers of culture and emotions. Research shows that, combined with modern design concepts, these traditional patterns can provide jewellery designers with rich creative inspiration, promote the innovation and diversification of modern jewellery design, and satisfy consumers' pursuit of personalization and cultural heritage. The study also found that this integration not only promotes the inheritance and innovation of traditional culture, but also enhances the market competitiveness and commercial value of jewellery brands, demonstrates the unique charm of Chinese culture, and promotes the diversified development of the jewellery market.